Co-infecting Reptarenaviruses Can Be Vertically Transmitted in Boa Constrictor - Keller, Saskia; Hetzel, Udo; Sironen, Tarja; Korzyukov, Yegor; Vapalahti, Olli; Kipar, Anja; Hepojoki, Jussi (PLoS pathogens, 2017)
Boid inclusion body disease (BIBD) is an often fatal disease affecting mainly constrictor snakes. BIBD has been associated with infection, and more recently with coinfection, by various reptarenavirus species (family Arenaviridae). Thus far BIBD has only been reported in captive snakes, and neither the incubation period nor the route of transmission are known. Herein we provide strong evidence that co-infecting reptarenavirus species can be vertically transmitted in Boa constrictor. In total we examined five B. constrictor clutches with offspring ranging in age from embryos over perinatal abortions to juveniles. The mother and/or father of each clutch were initially diagnosed with BIBD and/or reptarenavirus infection by detection of the pathognomonic inclusion bodies (IB) and/or reptarenaviral RNA. By applying next-generation sequencing and de novo sequence assembly we determined the "reptarenavirome" of each clutch, yielding several nearly complete L and S segments of multiple reptarenaviruses. We further confirmed vertical transmission of the co-infecting reptarenaviruses by species-specific RT-PCR from samples of parental animals and offspring. Curiously, not all offspring obtained the full parental "reptarenavirome". We extended our findings by an in vitro approach; cell cultures derived from embryonal samples rapidly developed IB and promoted replication of some or all parental viruses. In the tissues of embryos and perinatal abortions, viral antigen was sometimes detected, but IB were consistently seen only in the juvenile snakes from the age of 2 mo onwards. In addition to demonstrating vertical transmission of multiple species, our results also indicate that reptarenavirus infection induces BIBD over time in the offspring.